STRATEGI KEBIJAKAN PEMANFAATAN JASA LINGKUNGAN AIR SECARA BERKELANJUTAN DI TAMAN NASIONAL GUNUNG CIREMAI KUNINGAN-JAWA BARAT - Rismunandar Rismunandar (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Mount Ciremai National Park (TNGC) requires institutional policies for managing environmental services. This study aims to determine the sustainable management policy strategy for water environmental services, based on ecological, social and economical assessment. The approach used in this study is